Microwave-assisted organic synthesis : (Apple Academic Press Inc., 2015)
The large-scale production of chemicals to meet various societal needs has created environmental pollution, including pollution from byproducts and improper disposal of waste. With the world facing adverse consequences due to this pollution, green chemistry is increasingly being viewed as a means to address this concern. Since most organic synthese